(untitled) (Journal of Foreign Language Studies, 2024)
Within the scope of this paper, a further analysis was made of the art of using costume terminology by N. V. Gogol in his novel Dead Souls (Мертвые души), in order to highlight each characters’ personality as well as describe sceneries. This paper also analyses how the fate and traits of Russia were explained by using costume terminology as artistic details.